Average capacity analysis of FSO system with Airy beam as carrier over exponentiated Weibull channels - Li, Yi; Chu, Xingchun; Han, Zhongxiang; Tang, Hanling; Song, Xinkang (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
Based on scintillation index of Airy beam and exponentiated Weibull channel model, analytical expressions of average channel capacity for free-space optical (FSO) communication links with Airy beam as signal carrier under weak atmospheric turbulence and on-off keying modulation scheme are derived. The average capacity at various propagation distances, transverse scale factors and exponential decay factors has been evaluated. And we compared the average capacity of FSO links with Airy beam and Gaussian beam as signal carrier. The results show that the average capacity of FSO links with Airy beam as carrier increases with the increase of mean signal-to-noise ratio and decreases uniformly with the increase of propagation distance. When the transverse scale factor of Airy beam is about 2 cm, a higher average capacity can be obtained. And the smaller the exponential decay factor of Airy beam, the larger the average capacity. Under the same source power or source width, the average capacity of FSO links with Airy beam as carrier is significantly higher than that of FSO links with Gaussian beam as carrier. The results of this research have some reference significance for the application of Airy beam in FSO communication system.
Optica Applicata, Vol. 53, 2023, nr 1, s. 35-48
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; Airy beam; free-space optical communication; channel capacity; exponentiated Weibull model